O ensino de ciências naturais e a organização do currículo escolar: um estudo sobre a prática docente de professores dos anos iniciais do ensino fundamental - OLIVEIRA, Ana Júlia Viégas Gomes (2019)
The present master of dissertation has as its theme the study of Natural Sciences teaching in Elementary Years and the curricular organization and aims to investigate which teaching practices can be established for a curricular proposal, in which the teaching of sciences is an articulating component of theories and scientific practices that broaden world views favoring the formation of active and critical citizens. To base this work were brought the contributions of some authors of the area of Natural Sciences as Krasilchik (2000); (2002), Sacristán (2000), Didactics of the Natural Sciences, Geraldo (2009), and Educational Practice, the considerations of Zabala (1998). The field of study was a school in the city of Paço do Lumiar, Maranhão and the methodology was of the type of participant research, because during the research process there was interaction between the subjects surveyed teachers and students of the 5th grade elementary school. As the nature of the research is applied, because there was employment of knowledge in the course of the research. The approach of the study was qualitative and in relation to the specific objectives was exploratory. As a data collection technique, classroom observation, interview with teachers and focus groups with students were used. For data analysis and interpretation, categorization was used, in which it was possible to organize the answers in three categories of analysis for the interpretation of the data in light of the theoretical contributions used, field observations and responses of the interviews were organized in tables to highlight the similarities of the responses. It was noticed during the classes of Natural Sciences that there is predominance of an expositive teaching, in which there is not a concern in the diversification of the activities for the teaching of Sciences, in addition to which the curriculum of Natural Sciences is based predominantly in didactic book. Faced with this reality, in order to contribute to the development of new teaching practices in the teaching of Natural Sciences, the didactic Situation Book was elaborated with themes Natural Sciences for the 5th Elementary School, bringing didactic situations, with objects of knowledge related to the interests of the research subjects, in addition to being aligned with the National Common Base Curricular- BNCC. It is intended to enable the development of students with critical and reflexive postures.